Clinical Activity and Tolerability of SL-401 (Tagraxofusp): Recombinant Diphtheria Toxin and Interleukin-3 in Hematologic Malignancies - Omar Alkharabsheh; Arthur E. Frankel (Biomedicines, 2019)
Overcoming the leukemia stem cell resistance to intensive chemotherapy has been an area of extensive research over the last two decades. Advances and greater understanding of the molecular biology of leukemia stem cells are in rapid progress. Targeted therapies are currently being used in clinical practice with reasonable response rates, but a cure is being achieved in only a small percentage of patients, most likely due to tumor mutational heterogeneity. A genetically engineered diphtheria toxin fused with interleukin-3 (SL-401 or tagraxofusp) has shown robust activity in blastic plasmacytoid dendritic cell neoplasm and promising response rates in different myeloid malignancies, including eradication of minimal residual disease. Multiple clinical trials are being conducted using this drug and the preliminary results are encouraging. This article reviews the clinical trials for SL-401, its mechanism of action, clinical activity, and the adverse event profile.